2016
DOI: 10.1093/jme/tjw097
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Susceptibility ofOchlerotatus japonicus,Ochlerotatus triseriatus, Aedes albopictus,andAedes aegypti(Diptera: Culicidae) to La Crosse Virus

Abstract: Invasive mosquito species can increase the transmission risk of native mosquito-borne diseases by acting as novel vectors. In this study, we examined the susceptibility of three exotic invasive mosquito species Aedes aegypti (L.), Ae. albopictus (Skuse), and Ochlerotatus japonicus (Theobald) to La Crosse virus (LACV) relative to the native primary vector Ochlerotatus triseriatus (Say). Adult females of the four mosquito species were orally challenged with LACV; incubated for 3, 5, 7, 9, or 11 d; and their midg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…These community level changes can significantly alter vector-borne disease risk for many pathosystems. Aedes albopictus readily bites humans, and is a competent vector of myriad pathogens of global human health concern, including dengue virus, West Nile virus, chikungunya virus, and Zika virus [41,51], as well as pathogens of focal concern in North Carolina, including La Crosse virus [52,53]. The overall community simplification and increasing abundance of Ae .…”
Section: Discussionmentioning
confidence: 99%
“…These community level changes can significantly alter vector-borne disease risk for many pathosystems. Aedes albopictus readily bites humans, and is a competent vector of myriad pathogens of global human health concern, including dengue virus, West Nile virus, chikungunya virus, and Zika virus [41,51], as well as pathogens of focal concern in North Carolina, including La Crosse virus [52,53]. The overall community simplification and increasing abundance of Ae .…”
Section: Discussionmentioning
confidence: 99%
“…albopictus and Aedes geniculatus , with increasing number of mature follicles with increasing wing lengths [ 16 ]. For La Crosse virus infection, it was shown that female wing length of the Asian bush mosquito has no significant effect on the infection status [ 60 ]. The Asian bush mosquito is considered to be a minor vector for arbovirus transmission, and no wild-caught adult female was found to carry pathogens so far in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti mosquitoes were more susceptible to DENV infection, resulting in higher dissemination rates (frequency at which an arbovirus can infect and replicate in the midgut epithelial cells and cross over into the hemocoel) ([ 256 ], but see [ 257 ]). In contrast, a recent vector competence study of LACV in field collected Ochlerotatus triseriatus mosquitoes showed the opposite result, where infected females were larger than uninfected ones [ 258 ]. Increased larval competition also resulted in increased DENV infection rates in Ae.…”
Section: Other Sources Of Variationmentioning
confidence: 97%